2022
DOI: 10.26803/ijlter.21.10.23
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceived Enacted Pedagogical Content Knowledge in Biology at Selected Secondary Schools in Lusaka

Abstract: The pedagogical content knowledge (PCK) of teachers influences students’ achievement of the learning outcomes. This study examined teachers’ perceived enactment of PCK in biology. The quantitative survey design was adopted by using a Likert-scale questionnaire consisting of six components of PCK, namely curricular saliency, students’ prior knowledge, what makes the subject easy or difficult, representations, conceptual teaching strategies, and assessment. Data on teachers’ perceived enacted PCK (ePCK) were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The Statistical Package for the Social Sciences (SPSS) version 20 was used to analyse the data. The responses were treated as though they were continuous data, so that aggregated means and standard deviations were computed (Lai & Lin., 2018;Mapulanga et al, 2022b). Therefore, appropriate descriptive statistics (means and standard deviations) were used to describe students' perceptions of teachers' ePCK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Statistical Package for the Social Sciences (SPSS) version 20 was used to analyse the data. The responses were treated as though they were continuous data, so that aggregated means and standard deviations were computed (Lai & Lin., 2018;Mapulanga et al, 2022b). Therefore, appropriate descriptive statistics (means and standard deviations) were used to describe students' perceptions of teachers' ePCK.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results contradict with teachers' perceptions of their ePCK. For example, a previous study found that teachers had high perceptions of their PCK enactment (Mapulanga et al, 2022b). The difference in students' and teachers' perceptions needs to be investigated further.…”
Section: Students' Perceptions Of Teachers' Epckmentioning
confidence: 93%
“…Mean responses of 1-2.9 were considered low, those of 3-3-9 were considered moderate whereas 4-4.9 was considered high-level self-efficacy, with mean scores of five being considered very high-level self-efficacy. The classification of mean responses as low, high and very high were adopted from Mapulanga et al (2022) and applied to the context of this study.…”
Section: Instrument and Proceduresmentioning
confidence: 99%
“…Although there is abundant research on biology teachers' TSPCK (Bravo & Cofré, 2016;Mthethwa-Khunene, 2015;Nilsson & Karlsson, 2018: Park & Chen, 2012, fewer studies are investigating biology teachers' TSPCK in respiration (Mapulanga et al, 2022a;2022b). This is despite research showing that students face challenges and misconceptions about respiratory concepts (Dam et al, 2019).…”
Section: Research Problemmentioning
confidence: 99%
“…Furthermore, they also reported that the least integrated components were what makes the topic easy or difficult and representations. In another related study, Mapulanga et al (2022b) explored the Zambian teachers' perceptions of PCK enactment in biology. They concluded that the teachers' perception of their enacted PCK components was high except for the component -what makes the subject easy or difficult.…”
Section: Introductionmentioning
confidence: 99%